An amplification mechanism for weak ELF magnetic fields quantum-bio effects in cancer cells - Amirali Zandieh; Seyed Peyman Shariatpanahi; Amir Abas Ravassipour; Javad Azadipour; Maryam Sadat Nezamtaheri; Zahra Habibi-Kelishomi; Mojtaba Ghanizadeh; Ali Same-Majandeh; Keivan Majidzadeh-A; Amir Taheri; Alireza Madjid Ansari; Mohammad Amin Javidi; et al. (Scientific Reports)
Abstract Observing quantum mechanical characteristics in biological processes is a surprising and important discovery. One example, which is gaining more experimental evidence and practical applications, is the effect of weak magnetic fields with extremely low frequencies on cells, especially cancerous ones. In this study, we use a mathematical model of ROS dynamics in cancer cells to show how ROS oscillatory patterns can act as a resonator to amplify the small effects of the magnetic fields on the radical pair dynamics in mitochondrial Complex III. We suggest such a resonator can act in two modes for distinct states in cancer cells: (1) cells at the edge of mitochondrial oscillation and (2) cells with local oscillatory patches. When exposed to magnetic fields, the first group exhibits high-amplitude oscillations, while the second group synchronizes to reach a whole-cell oscillation. Both types of amplification are frequency-dependent in the range of hertz and sub-hertz. We use UV radiation as a positive control to observe the two states of cells in DU and HELA cell lines. Application of magnetic fields shows frequency-dependent results on both the ROS and mitochondrial potential which agree with the model for both type of cells. We also observe the oscillatory behavior in the time-lapse fluorescence microscopy for 0.02 and 0.04 Hz magnetic fields. Finally, we investigate the dependence of the results on the field strength and propose a quantum spin-forbidden mechanism for the effect of magnetic fields on superoxide production in QO site of mitochondrial Complex III.